AB0579 Immunological results of salivary gland biopsy and their relationship with clinical and serological parameters in primary sjÖgren's syndrome. (12th June 2018) - Park, H.S.; Martinez Martinez, L.; Magallares, B.; Fernandez Castro, M.; Martin, M.A.; Sanchez Alonso, F.; Castellví, I.; Laiz, A.; Diaz-Torne, C.; Millan Arciniegas, M.; Moya Alvarado, P.; Lopez Vilaro, L.; et al.
Abstract : Background: Positive minor salivary gland biopsy(MSGB) is a major criteria for the diagnosis of primary Sjögren's Syndrome (PSS). In our centre the MSGB analysis is carried out by Immunology and Pathology Department in parallel. The immunological analysis identifies the lymphocytic composition of the inflammatory infiltrate. Their results show: the number of T and B cells, the ratio between CD4 and CD8 T lymphocytes and other non infiltrating lymphocytes. Objectives: The goal of our study was to evaluate whether there is an association between the lymphocytic composition of the MSGB with the clinical and serological findings of PSS patients. Methods: Patients diagnosed of PSS according American-European criteria(2002) underwent . MSGB between February and November of 2017 Demographic (sex and age), clinical (disease duration, xerostomía, queratoconjuctivitis sicca, Schirmer test, systemic disease) data were collected. Present or previous treatment with steroids and/or immunosuppressive therapy, serological studies such as ANA, RF, anti Ro and anti La were also included. MSGB data with the number of infiltrates, quantitative composition of T and B lymphocytes, CD4/CD8 ratio and presence of other non infiltrating lymphocytes were registered. Pathology data concerning Chisholm-Mason scale, presence of fibrosis, atrophy and size of infiltrate (small, moderate and severe) were also registered. A multiple logistic regression for each item of the immunological analysis adjusted for sex and age was made. We also measured the odds ratio and performed correlation test for all variables included. Results: Table 1 and 2 summarise our cohort characteristics. The presence of T lymphocyte was associated with B lymphocyte, OR 99.21 (IC95% 5.12–1921, p=0.002) and with higher CD4/CD8 ratio, OR 17.34 (IC95% 1.45–206.15, p=0.024). CD4/CD8 ratio was also associated with the presence of T lymphocytes OR 10.54 (IC95% 2.16–51.50, p=0.004) and B lymphocytes were associated with the presence of T lymphocytes as well OR 5.38 (CI95% 1.63–17.72, p=0.006). Other non infiltrating lymphocytes were composed of CD8 T cells and were associated with a positive Schirmer test OR 17.47(IC95% 1.62–188.13, p=0.018) but inversely associated with Chisholm-Mason grade ≥3 OR 0.09(IC95% 0.014–0.58, p=0.011). There was no other association observed with clinical or analytical parameters. Colinearity test between pathological and immunological analysis was negative. Conclusions: MSGB in our PSS patients demonstrated an association between T lymphocytes, B lymphocytes and CD4/CD8 ratio. The infiltrate is mostly based on CD4 more than CD8 T cells. Other significant findings were the association between CD8 T lymphocytes and Chisholm-Mason scale grade ≥3, regardless of the number of infiltrates. No correlation or colinearity was observed with the number of infiltrates by immunological analysis and the Chisholm-Mason grade reported by the pathology analysis. Disclosure of Interest: None declared